REPRESENTASI NILAI-NILAI BHINNEKA TUNGGAL IKA DALAM FILM TABULA RASA (ANALISIS SEMIOTIKA ROLAND BARTHES) - Nabila Putri Aldira; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Film is a media of mass communication that still have audiences until now. Film have some functions such as informative, educative, and persuasive. Beside it, film also become a media of life representation. Researcher lift a film entitled Tabula Rasa that representation unity in diversity values within. Tabula Rasa is a film that merge unity in diversity values between the characters. Tabula Rasa storied about struggle in life of nomads from two provinces in Indonesia. Within different things, they are can melted and re-found their dreams because of foods. The goal of this research is to know the meaning of denotation, connotation, and myth by Roland Barthes that have in Tabula Rasa film. Beside it, to know the values of unity in diversity representation in Tabula Rasa film.The research method is cualitative that referring to semiotics analysis of Roland Barthes. The subject of the research is values of unity in diversity with research object is Tabula Rasa film. Barthes describes 3 his opinions that denotation, describes about signifier and signified in reality with explicit meaning. Connotation describes about signifier and signified related in non-reality with implicit meaning. And myth describes about customs and reliance applied in society.The result of this research show that scenes researched related with the meaning of denotation, connotation, and myth by Roland Barthes. And the result also shows that have the representation of unity in diversity values in Tabula Rasa film are inclusive behavior, accomodate pluralistic character, not looking for his own win, deliberation to reach consensus, based on love and willing to sacrifice. From those 5 indicators researcher found the values of unity in diversity deeply and detail such as cultural diversity of nation, tolerance to differences, democracy, and to help each other.Keyword : Representation, Film, Unity in Diversity